2020
DOI: 10.1126/sciadv.abc0418
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into ADP-ribosylation of ubiquitin by Deltex family E3 ubiquitin ligases

Abstract: Cellular cross-talk between ubiquitination and other posttranslational modifications contributes to the regulation of numerous processes. One example is ADP-ribosylation of the carboxyl terminus of ubiquitin by the E3 DTX3L/ADP-ribosyltransferase PARP9 heterodimer, but the mechanism remains elusive. Here, we show that independently of PARP9, the conserved carboxyl-terminal RING and DTC (Deltex carboxyl-terminal) domains of DTX3L and other human Deltex proteins (DTX1 to DTX4) catalyze ADP-ribosylation of ubiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 73 publications
4
91
1
Order By: Relevance
“…During the completion of this study, it was reported that Ub Gly 76 ADP-ribosylation can be reversed in vitro by deubiquitinases (DUBs) (Chatrin et al, 2020). DUBs are not, however, the typical erasers of ADP-ribosylation and three families of ADP-ribosylation erasers have been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the completion of this study, it was reported that Ub Gly 76 ADP-ribosylation can be reversed in vitro by deubiquitinases (DUBs) (Chatrin et al, 2020). DUBs are not, however, the typical erasers of ADP-ribosylation and three families of ADP-ribosylation erasers have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…A ~200 amino acid C-terminal fragment of DTX3L (aa 557-740) was shown by Chatrin et al to ADP-ribosylate Ub in vitro (Chatrin et al, 2020). We therefore compared the activities of the DTX3L fragment to that of full-length DTX3L and the DTX3L-PARP9 heterodimer (Fig.…”
Section: Dtx3l Adp-ribosylates Ubiquitin In the Absence Of Parp9mentioning
confidence: 99%
“…It also has been regarded as a component of a ubiquitinating LPS-responsive protein complex suggesting a role in LPS-mediated macrophage activation [ 125 ]. Surprisingly, Chatrin and colleagues [ 126 ] showed that the ART activity on ubiquitin’s Gly76 is not provided by ARTD9 but by the conserved carboxyl-terminal RING and DTC (deltex carboxyl-terminal) domains of DTX3L and other human deltex proteins (DTX1 to DTX4). Indeed, Yang and colleagues [ 123 ] made their observation in the context of DTX3L/ARTD9 heterodimer, but not of DTX3L on its own.…”
Section: Mono(adp-ribosyl) Transferases (Mart)mentioning
confidence: 99%
“…The human Deltex E3 ligases—DTX3L, DTX1, and DTX4—also catalyze the ADP-ribosylation of ubiquitin on Gly76 using the E2-ubiquitin thioester complex; this ADP-ribosylation does not exert a toxin function but rather contributes to the regulation of cellular processes via crosstalk between ADP-ribosylation and ubiquitination [ 49 , 50 ]. Deltex proteins have a conserved RING domain, which is characteristic of a RING-type E3 ligase and a Deltex carboxyl-terminal (DTC) domain in the C-terminus.…”
Section: Other Artsmentioning
confidence: 99%
“…Deltex forms a heterodimer with PARP9, which is a mono-ADP-ribosyltransferase reported to be enzymatically inactive, and Yang, C.-S. et al reported that the heterodimer ADP-ribosylates the carboxyl group of ubiquitin Gly76, which is normally used for the conjugation of ubiquitin to protein substrates [ 49 ]. However, it was recently reported that this ADP-ribosylation is PARP9-independent, in that it requires only the RING and DTC domains of the Deltex protein [ 50 ]. Although the precise mechanism underlying this ADP-ribosylation remains unclear, the following mechanism is herein proposed: The E2-ubiquitin thioester complex binds to the RING domain, and the thioester bond is hydrolyzed to release ubiquitin.…”
Section: Other Artsmentioning
confidence: 99%